The Landscape of Social Enterprise in the Slovak Republic - Polačková, Zuzana (Social Enterprise in Central and Eastern Europe, 2021)
The first legal definition of social enterprise (SE) was adopted in 2008 as part of the employment policy; it is one of the reasons why social enterprises in Slovakia are often narrowly associated with work integration. The growing recognition of the cooperative movement was interrupted by political changes in 1948, when a brutal and massive nationalisation process was launched. The cooperative idea was co-opted for the purposes of the ideological advocacy of socialism, and cooperatives were incorporated into the state-controlled planned economic system. The Revolution of November 1989 introduced new socio-political conditions in the country, and a strong antagonism emerged against the cooperative concept, which was considered at the time as a synonym for socialism. The recognition of social entrepreneurship among the general public was gradually growing, though. A specific segment of the SE sector in Slovakia, which deserves special attention, is that of “municipal social enterprises”.